Abrus Precatorius Toxicity Presenting with Diarrhoea and Encephalopathy: A Case Report (Nepal Medical College Journal, 2020)
Infective etiologies are the first differentials that come to the mind in clinical conditions presenting with diarrhea associated with encephalopathy. We report a case of a 21 year old lady diagnosed as acute infective gastroenteritis and treated for the same only to manifest itself later as encephalopathy leading to a diagnostic dilemma. The clinical manifestations had started from abdominal cramps, bloody diarrhea followed by altered sensorium. A detailed history later revealed the use of the roots of Abrus precatorius for the treatment of sub-fertility was the missing piece of the diagnostic puzzle. Only after confirmation of the herb did the temporal sequence of events seemed logical. The patient was successfully managed for toxic acute disseminated encephalomyelitis (ADEM). Abrus precatorius is a commonly used herb used in traditional medicinal practice in many cultures. Various aspects of its toxicity can mimic other more commonly encountered medical ailments.